1992
DOI: 10.1002/j.1460-2075.1992.tb05198.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of two U3 binding sites on yeast pre-ribosomal RNA.

Abstract: It has long been known that U3 can be isolated hydrogen bonded to pre‐ribosomal RNAs, but the sites of interaction are poorly characterized. Here we show that yeast U3 can be cross‐linked to 35S pre‐rRNA both in deproteinized extracts and in living cells. The sites of cross‐linking were localized to the 5′ external transcribed spacer (ETS) and then identified at the nucleotide level. Two regions of U3 near the 5′ end are cross‐linked to pre‐rRNA in vivo and in vitro; the evolutionarily conserved box A region a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
220
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(228 citation statements)
references
References 35 publications
8
220
0
Order By: Relevance
“…The only component currently known to be required for cleavage at site A 0 is the U3 (Hughes & Ares, 1991)+ This function requires base pairing between the U3 snoRNA and a sequence in the pre-rRNA 59 ETS that lies 130 nt upstream of A 0 (Beltrame & Tollervey, 1992+ It was proposed that the U3/59 ETS interaction targets the endonuclease to its cleavage site (Abou Elela et al+, 1996)+ This remains an attractive model, but an endonuclease other than Rnt1p must now be sought+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only component currently known to be required for cleavage at site A 0 is the U3 (Hughes & Ares, 1991)+ This function requires base pairing between the U3 snoRNA and a sequence in the pre-rRNA 59 ETS that lies 130 nt upstream of A 0 (Beltrame & Tollervey, 1992+ It was proposed that the U3/59 ETS interaction targets the endonuclease to its cleavage site (Abou Elela et al+, 1996)+ This remains an attractive model, but an endonuclease other than Rnt1p must now be sought+…”
Section: Discussionmentioning
confidence: 99%
“…For Rnt1p depletion cells were harvested at intervals following the shift from RSG medium (2% galactose, 2% sucrose, 2% raffinose) to medium containing 2% glucose+ RNA was extracted as described previously (Tollervey & Mattaj, 1987)+ Northern hybridization (Tollervey, 1987) and primer extension (Beltrame & Tollervey, 1992) were as described previously+ Standard 1+2% agarose/formaldehyde and 6% or 8% acrylamide gels were used to analyze the high and low molecular weight rRNA species and primer extension reactions+ For pre-rRNA hybridization and primer extension, oligonucleotides depicted in Figure 1A were used: 001, 59-CCAGTTACGAAAATTCTTG; 002, 59-GCTCTTTGCTCTTGCC; 005, 59-ATGAAAACTCCACAGTG; 007, 59-CTCCGCTTATTGATATGC; 008, 59-CATGGCTTAATCTTTGAGAC; 013, 59-GGCCAGCAATTTCAAGTTA; 015, 59-TTTCGCTGCGTTCTTCATC; 022, 59-GAAATAAAAAACAAATCAGAC; 026; 59-CCAGATAACTATCTTAAAAG; 053, 59-TGGTACACTCTTACACAC; 054, 59-AACCCATCTTTGCAACGA+ For detection of the excised A 0 -A 1 fragment, a riboprobe complementary to the region between sites A 0 and A 1 was generated as previously described + For hybridization to RNT1, mRNA oligonucleotide anti-RNT1 was used, 59-GCCTTTGTTGGGTCATAGCTATCTTCTCCT TCGTC+…”
Section: Rna Extraction Northern Hybridization and Primer Extensionmentioning
confidence: 99%
“…In eukaryotic cells, synthesis and processing of ribosomal RNAs (rRNAs) and assembly of ribosomes occur in the nucleolus and follow an unusually complex pathway+ The 18S, 5+8S, and 25-28S rRNAs are synthesized as a single precursor (pre-rRNA), which contains additional sequences that are discarded during RNA maturation+ The maturation process involves extensive modification of rRNA nucleotides, most of them guided by small nucleolar RNAs (snoRNAs), followed by multiple cleavage events resulting in the formation of different processing intermediates+ The substrate for rRNA processing is a large ribonucleoprotein complex containing a multitude of ribosomal proteins and accessory nucleolar trans-acting factors that associate with the nascent pre-rRNA (reviewed by Kressler et al+, 1999;Venema & Tollervey, 1999;Lewis & Tollervey, 2000)+ rRNA processing has been most extensively studied in the yeast Saccharomyces cerevisiae and many trans-acting factors, both proteins and ribonucleoproteins, required for the process have been characterized+ These include, in addition to guide snoRNAs, the ribonucleoprotein RNase MRP, the essential snoRNAs U3, U14, snR30 and snR10, and many proteins, which either act in association with snoRNAs or function independently+ Among the latter are putative ATPdependent RNA helicases, Dim1p methylase, and endoand exoribonucleases (Kressler et al+, 1999;Venema & Tollervey, 1999)+ Despite substantial progress in identification of the trans-acting factors required for pre-rRNA processing, their precise functions remain largely unknown+ The factor best characterized to date is the U3 snoRNP+ Based on results from yeast and vertebrate systems, it appears that U3 snoRNP plays a central role in the assembly of the machinery responsible for processing of 18S rRNA and biogenesis of the 40S ribosomal subunit (Beltrame & Tollervey, 1992;Mougey et al+, 1993;Venema & Tollervey, 1999;Borovjagin & Gerbi, 2000, and references therein)+ U3 snoRNA base pairs with the 35S pre-rRNA within the 59 external transcribed spacer (ETS) and the 59 part of 18S rRNA and is required for early cleavages at the processing sites A 0 , A 1 , and A 2 (Beltrame & Tollervey, 1995;Sharma & Tollervey, 1999;Venema & Tollervey, 1999, and references therein)+ The yeast U3 snoRNP has recently been shown to contain five strongly associated structural proteins (Watkins et al+, 2000)+ However, consistent with the central role of U3 snoRNP in rRNA maturation, immunoprecipitation (IP) experiments revealed many additional proteins associating with the particle+ These include Sof1p, Mpp10p, Imp3p, Imp4p, Dhr1p, Lcp5p, and Rcl1p (Jansen et al+, 1993;Dunbar et al+, 1997;Wiederkehr et al+, 1998;Lee & Baserga, 1999;…”
Section: Introductionmentioning
confidence: 99%
“…The nucleolus of eukaryotic cells contains a wide array of stable small nucleolar RNPs (snoRNPs) involved in processing of ribosomal RNA transcripts and in ribosome assembly (Kressler et al+, 1999;Venema & Tollervey, 1999)+ The most abundant of the snoRNPs required for processing of pre-rRNA, the U3 snoRNP, has been studied in a number of different organisms+ Functional studies on the role of the U3 snoRNA in mice, Xenopus laevis, or Saccharomyces cerevisiae have revealed that the U3 snoRNA is required for pre-18S rRNA processing (Kass et al+, 1990;Savino & Gerbi, 1990;Hughes & Ares, 1991;Mougey et al+, 1993;Borovjagin & Gerbi, 1999)+ In yeast cells, the U3 snoRNA base pairs with the pre-rRNA at two sites and is required for endonucleolytic cleavage at sites A0, A1, and A2 leading to 18S rRNA production (Hughes & Ares, 1991;Beltrame & Tollervey, 1992, 1995Beltrame et al+, 1994;Hughes, 1996;Sharma & Tollervey, 1999)+ Comparison of the U3 snoRNAs among eukaryotic organisms has revealed several conserved sequence elements called boxes A, A9, B, C, C9, and D (Fig+ 1A;Wise & Weiner, 1980;Jeppesen et al+, 1988;Porter et al+, 1988;Tyc & Steitz, 1989;Kiss & Solymosy, 1990;Myslinski et al+, 1990;Hughes & Ares, 1991;Marshallsay et al+, 1992;Tycowski et al+, 1993)+ Secondary structure models for the U3 snoRNA have been proposed from a variety of U3 molecules based on computer folding, phylogenetic sequence comparison, and chemical and enzymatic mapping; yet, no consensus structure has emerged (Kiss et al+, 1985;Hughes et al+, 1987;Parker & Steitz, 1987;Jeppesen et al+, 1988;Porter et al+, 1988;Kiss & Solymosy, 1990;Myslinski et al+, 1990;…”
Section: Introductionmentioning
confidence: 99%
“…The hinge region, the spacing between the 59 and 39 domains of the U3 snoRNA, is one of the least understood segments of the U3 snoRNA+ In yeast, the hinge region encompasses nt 39 to 72+ A hairpin called helix 1b9 has been proposed to exist in snoRNPs in solution within these boundaries (Segault et al+, 1992;Mereau et al+, 1997)+ Helix 1b9 is sometimes drawn as part of a larger helix termed helix 1b or stem-loop 1b (Segault et al+, 1992;Mereau et al+, 1997;Antal et al+, 2000)+ Although the primary sequence of the hinge region differs among eukaryotic organisms, its length is fairly well conserved (between 34 and 37 nt; Samarsky & Fournier, 1998)+ The 59 portion of the hinge region (nt 39-48) base pairs with the pre-rRNA as a prerequisite for the cleavage reaction at A0 (Beltrame & Tollervey, 1992, 1995Beltrame et al+, 1994)+ Therefore portions of both the 59 domain and the hinge region base pair with the pre-rRNA to effect pre-rRNA cleavage+ Because of these RNA-RNA interactions, the two hairpins in the 59 domain and hinge region of the U3 snoRNA are not likely to exist in vivo (Antal et al+, 2000;Borovjagin & Gerbi, 2000)+ The U3 snoRNA is complexed with both proteins common to box C/D snoRNPs and proteins specific for the U3 snoRNP+ The common proteins, conserved from yeast to humans, are fibrillarin (Nop1p), Nop56p, Nop5/ Nop58p, and Snu13p (Schimmang et al+, 1989;Henriquez et al+, 1990;Tollervey et al+, 1991Tollervey et al+, , 1993Gautier et al+, 1997;Wu et al+, 1998;Lafontaine & Tollervey, 1999;Watkins et al+, 2000)+ In addition, the U3 snoRNP contains at least seven other proteins that are not components of any other snoRNP-Sof1p, Mpp10p, Imp3p, Imp4p, Lcp5p, Rrp9p, and Dhr1p (Jansen et al+, 1993;Dunbar et al+, 1997;Wiederkehr et al+, 1998;Wu et al+, 1998;Lee & Baserga, 1999;Colley et al+, 2000;Venema et al+, 2000)+ Mpp10p, Imp3p, Imp4p, Rrp9p, and the common proteins have known metazoan homologs (Gautier et al+, 1997;Pluk et al+, 1998;…”
Section: Introductionmentioning
confidence: 99%